Pharmacoeconomic Analysis of Treating Lung Cancer with Different Regimens Using the Cheapest and Costliest Brand and the Generic Jan Aushadhi Drugs Marketed in India - Krishna, Abhishek; Palatty, Princy Louis; George, Thomas; Baliga, Manjeshwar Shrinath (Indian Journal of Medical and Paediatric Oncology, 2024)
Background/Purpose of the Study The costs of chemotherapy drugs which are vital in the treatment of lung cancer can be exorbitant. The current study was undertaken to ascertain cost minimization analysis by comparing costliest and cheapest branded with Jan Aushadhi (JA) drugs marketed in India.Methods The cost of costliest, cheapest branded, and JA drugs were collected from the designated reference sites. The cost difference, cost ratio, and percentage of cost variation were calculated as per cost minimization study guidelines.Results The results of the analysis suggest that the JA drugs were much cheaper than the branded drugs and when used in regimens resulted in substantial cost savings. The biggest financial advantage was seen in the commonly used cisplatin–pemetrexed regimen where cost saving of Rs. 268,002 was observed for the whole treatment of six cycles. Using JA drugs also reduced the cost for the targeted therapy with gefitinib and erlotinib.Conclusion The cost minimization study, which is the first in this field of lung cancer, clearly indicates the usefulness of JA drugs in reducing financial costs for the patient.
Keywords: lung cancer; anticancer drugs; pharmacoeconomics; Jan Aushadhi; cost difference; cost ratio; percentage of cost variation